Estudo de metodologias para determinar perdas físicas em redes de distribuição de água - Viegas, José Vilmar (2003)
This study presents an evaluation and comparison of the most important methodologies to estimate water losses of a sector of supply through its components, in specially, the physical losses. By revision of the literature it was tried to demonstrate the theoretical foundations of the several available methods for the resolution of these estimates that become very important in projects of operational improvement of a system. It is stood out, in this study, the EPANET model, a hydraulic modelling developed to simulate leaks and demand flows of a sector of water distribution starting from parameters characteristic of the sector. This model was selected for the verification of its appliability condition and for comparison with the empiric method “FND-Factor Night-Day”. The revision of the literature shows that the night minimum flow is adopted universally to generate the parameters that relate flow x pressure and the determination of physical losses. The development of this study used the night minimum flow to estimate the exponent N, the coefficient of discharge CD and the night losses physics through methodologies related in the literature. The exponent N, that relates leakage flow and pressure was estimated applying a quite simple method but that is based in the most modern concepts (FAVAD - Fixed and Variable Area Discharge Paths). The data collected in field allow the determination of the exponent characteristic of the sector that is used in all the presented methodologies. It is, also, stood out, the ease and the accuracy of FND - Factor Night-Day's application method that estimates daily physical losses starting from the night leakage flows and of the hourly factor. The results of the application of these models, hydraulic and empiric simulation, in the same base of data, space and in the time assured confidence in the aplication of each method. It was concluded, then, that the EPANET modelling presented good performance in the estimate of leakage and demands flow and its results are in conformity with presented for the FND-Factor Night-Day method and the annual “Water Balance” indicating to be an important tool for the taking of decision about the actions destined to the combat of the water losses of the which stand out the control of active leakage and the unauthorized consumption .